Formation of semiconductor quantum dots for electrochemiluminescent assay by laser fragmentation - Zholudov, Yu. T.; Vasylkovskyi, V. S.; Slipchenko, M. I.; Slipchenko, O. V.; Chichkov, B. N. (ХНУРЕ, 2019)
The work describes the use of semiconductor quantum dots (QDs) for electrochemiluminescent assay of amine compaunds and development of the new method for production of shell-free semiconductor nanoparticles using laser fragmentation technique.
Keywords: quantum dot; laser fragmentation